miR-219 Cooperates with miR-338 in Myelination and Promotes Myelin Repair in the CNS - Wang, Haibo; Moyano, Ana Lis; Ma, Zhangyan; Deng, Yaqi; Lin, Yifeng; Zhao, Chuntao; Zhang, Liguo; Jiang, Minqing; He, Xuelian; Ma, Zhixing; Lu, Fanghui; Xin, Mei; et al. (Developmental cell, 2017)
A lack of sufficient oligodendrocyte myelination contributes to remyelination failure in demyelinating disorders. miRNAs have been implicated in oligodendrogenesis; however, their functions in myelin regeneration remained elusive. Through developmentally regulated targeted mutagenesis, we demonstrate that miR-219 alleles are critical for CNS myelination and remyelination after injury. Further deletion of miR-338 exacerbates the miR-219 mutant hypomyelination phenotype. Conversely, miR-219 overexpression promotes precocious oligodendrocyte maturation and regeneration processes in transgenic mice. Integrated transcriptome profiling and biotin-affinity miRNA pull-down approaches reveal stage-specific miR-219 targets in oligodendrocytes and further uncover a novel network for miR-219 targeting of differentiation inhibitors including Lingo1 and Etv5. Inhibition of Lingo1 and Etv5 partially rescues differentiation defects of miR-219-deficient oligodendrocyte precursors. Furthermore, miR-219 mimics enhance myelin restoration following lysolecithin-induced demyelination as well as experimental autoimmune encephalomyelitis, principal animal models of multiple sclerosis. Together, our findings identify context-specific miRNA-regulated checkpoints that control myelinogenesis and a therapeutic role for miR-219 in CNS myelin repair. [Display omitted] •miR-219 is critical for oligodendrocyte differentiation and myelination in murine CNS•miR-338 deletion exacerbates the dysmyelination phenotype in miR-219-deficient mice•miR-219 targets stage-specific inhibitors and Lingo1-Etv5 to promote CNS myelination•miR-219 mimics augment remyelination and functional recovery in demyelinating models Wang et al. show that miR-219 collaborates with miR-338 and is required for proper oligodendrocyte differentiation and myelination in the mammalian CNS by targeting a network of stage-specific differentiation inhibitors, including Lingo1 and Etv5. Therapeutic delivery of miR-219 also enhances myelin repair in animal models of multiple sclerosis.